2011
DOI: 10.1007/s10762-011-9811-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Analysis of THz Surface Plasmon Polariton Waves with the Integrated Sub-wavelength Aperture Probe

Abstract: We demonstrate that the integrated sub-wavelength aperture probe designed for THz near-field scanning probe microscopy can be used to map surface plasmon waves at THz frequencies. Observed near-field images of metallic patterns reveal surface plasmon waves superimposed over THz transmission images. We discuss the coupling mechanism for the surface waves and arrive to an important conclusion that the detected surface wave images represent the spatial derivative of the surface plasmon electric field. The relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…3,4 In this THz microscopy system, a flat metallic surface with a small aperture is interacting with the antenna. It was found that placing the metallic plane of the probe close to a surface, which supports a Z-TSW, enhances the field of this wave (by of factor of 10 for a 3 lm separation between antenna and the probe) whereas the wave properties (the angular distribution of wave vectors) remain determined by the supporting surface geometry and stay practically unaffected by the metallic plane of the probe.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3,4 In this THz microscopy system, a flat metallic surface with a small aperture is interacting with the antenna. It was found that placing the metallic plane of the probe close to a surface, which supports a Z-TSW, enhances the field of this wave (by of factor of 10 for a 3 lm separation between antenna and the probe) whereas the wave properties (the angular distribution of wave vectors) remain determined by the supporting surface geometry and stay practically unaffected by the metallic plane of the probe.…”
mentioning
confidence: 99%
“…A subwavelength size particle is attached to the surface of one of the bow-tie arms and the sample is scanned (together with the output end of the waveguide) with respect to an integrated sub-wavelength aperture THz NF probe. 3,4,26,27 The THz NF probe has an aperture of d ¼ 10 lm and an integrated photoconductive antenna detector. 23,27 The overall spatial resolution of this NF probe is determined by the aperture size and the distance to the sample.…”
mentioning
confidence: 99%
See 3 more Smart Citations